On the taxonomy of the Zodarion thoni species-group (Araneae, Zodariidae), with description of a new species with an unmodified embolus - Dimitrov, Dragomir (Zootaxa, 2024)
A new species of Zodarion, belonging to Z. thoni-group, is described from the Taurus Mountains, Turkey. By now, it is the only known species with an unmodified embolic tip in this group. The syntypes of Z. rhodiense Caporiacco, 1948, Z. nigrifemur Caporiacco, 1948, and the holotype of Z. granulatum Kulczyński, 1908 are revised. Zodarion rhodiense sp. reval. is revalidated and Z. nigrifemur syn. n. is assigned as its junior synonym.